'Nobody really gets it': a qualitative exploration of youth mental health in deprived urban areas. Issue 5 (23rd June 2014) - Schaffalitzky, Elisabeth; Leahy, Dorothy; Armstrong, Claire; Gavin, Blanaid; Latham, Linda; McNicholas, Fiona; Meagher, David; O'Connor, Ray; O'Toole, Thomas; Smyth, Bobby P.; Cullen, Walter
Abstract: Aim: To examine the experience of developing and living with mental health and substance use disorders among young people living in urban‐deprived areas in Ireland to inform primary care interventions. Method: Semi‐structured qualitative interviews with 20 young adults attending health and social care agencies in two deprived urban areas, and analysed using thematic analysis. Results: Five themes were identified: experiencing symptoms, symptom progression, delay accessing help, loss of control/crisis point, and consequences of mental health and substance use disorders. As young people delayed help, symptoms disrupted normal life progression and they found themselves unable to engage in everyday activities, and living with reduced potential. Living in deprived areas influenced the development of problems: many had added stressors, less familial support and early exposure to violence, addiction and bereavement. Conclusion: Young people in urban‐deprived areas are especially vulnerable to mental health and substance use disorders. Early identification in primary care appears necessary in halting symptom and illness progression, improving young people's chances of achieving their potential.